Apparent diffusion coefficient in the evaluation of cerebral gliomas malignancy - Ignjatović, Jelena; Stojanov, Dragan; Živković, Vladimir; Ljubisavljević, Srđan; Stojanović, Nebojša; Stefanović, Ivan; Benedeto-Stojanov, Daniela; Ignjatović, Nebojša; Petrović, Slađana; Aracki-Trenkić, Aleksandra; Radovanović, Zoran; Lazović, Lazar (Vojnosanitetski pregled, 2015)
Background/Aim. Magnetic resonance imaging (MRI) is a key modality not only for lesion diagnosis, but also to evaluate the extension, type and grade of the tumor. Advanced MRI techniques provide physiologic information that complements the anatomic information available from conventional MRI. The aim of this study was to determine whether there is a correlation between apparent diffusion coefficient (ADC) maps of intracranial glial tumors and histopathologic findings and whether ADCs can reliably distinguish low-grade from high-grade gliomas. Methods. This retrospective study included 25 patients with MRI examination up to seven days before surgery, according to the standard protocol with the following sequences: T1WI, T2WI, FLAIR, DWI and post contrast T1WI. Data obtained from DW MRI were presented by measuring the value of ADC. The ADC map was determined by utilizing Diffusion-Perfusion (DP) Tools software. All the patients underwent surgical resection of the tumor. Histological diagnosis of tumors was determined according to the World Health Organization (WHO) classification. The ADC values were compared with the histopathologic findings according to the WHO criteria. Results. The ADC values of astrocytomas grades I (0.000614 ± 0.000032 mm2/s) were significantly higher (< 0.001) than the ADC values of anaplastic astrocytomas (0.000436 ± 0.000016 mm2/s) and the ADC values of glioblastomas multiforme (0.000070 ± 0.000008 mm2/s). The ADC values of astrocytomas grades II (0.000530 ± 0.000114 mm2/s) were significantly higher (< 0.001) than the ADC values of anaplastic astrocytomas (0.000436 ± 0.000016 mm2/s) and glioblastomas multiforme (0.000070 ± 0.000008 mm2/s). The ADC values of anaplastic astrocytomas (0.000436 ± 0.000016 mm2/s) were significantly higher (< 0.001) than the ADC values of glioblastomas multiforme (0.000070 ± 0.000008 mm2/s). The ADC values in the cystic part of the tumor for astrocytomas grades I (0.000775 ± 0.000023 mm2/s) were significantly higher (< 0.001) than the ADC values of anaplastic astrocytomas (0.000119 ± 0.000246 mm2/s) and glioblastomas multiforme (0.000076 ± 0.000004 mm2/s). The ADC values astrocytomas grades II (0.000511 ± 0.000421 mm2/s) were significantly higher (< 0.001) than the ADC values of glioblastomas multiforme (0.000076 ± 0.000004 mm2/s). Concluson. DWI with calculation of ADC maps can be regarded as a reliable useful diagnostic tool, which indirectly reflects the proliferation and malignancy of gliomas. The ADCs maps can both predict the results of histopathological tumor and distinguish between low- and high-grade gliomas, and provide significant information for presurgical planning, treatment and prognosis for patients with high-grade astrocytomas.